2021
DOI: 10.1111/jdv.16981
|View full text |Cite
|
Sign up to set email alerts
|

Continuous glucose monitoring systems give contact dermatitis in children and adults despite efforts of providing less ‘allergy‐ prone’ devices: investigation and advice hampered by insufficient material for optimized patch test investigations

Abstract: Background Medical devices are increasingly being reported to cause contact allergic dermatitis reactions. Objective Review of patients with diabetes type I referred for suspected allergic contact dermatitis to insulin pump or glucose sensor systems. Method: We have reviewed 11 referred diabetes mellitus patients investigated for allergic contact dermatitis reactions to medical devices and specifically Dexcom G6®. Extracts from the medical devices were analysed. Results The majority of patients was children, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
60
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(68 citation statements)
references
References 29 publications
6
60
0
1
Order By: Relevance
“…Figure 3 shows chromatograms and mass spectra of an adhesive patch extract and a 2,2 0 -methylenebis(6-tert-butyl-4-methylphenol) monoacrylate reference sample. All extracts also contained isobornyl acrylate (IBOA) at estimated concentrations in the same order of magnitude as those found in previously analyzed sensors from older batches, 2 corresponding to a total IBOA content of ≤1 μg/patch and ≤1 μg/sensor housing. Furthermore, all sensors were also found to contain 2,2 0methylenebis(6-tert-butyl-4-methylphenol).…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…Figure 3 shows chromatograms and mass spectra of an adhesive patch extract and a 2,2 0 -methylenebis(6-tert-butyl-4-methylphenol) monoacrylate reference sample. All extracts also contained isobornyl acrylate (IBOA) at estimated concentrations in the same order of magnitude as those found in previously analyzed sensors from older batches, 2 corresponding to a total IBOA content of ≤1 μg/patch and ≤1 μg/sensor housing. Furthermore, all sensors were also found to contain 2,2 0methylenebis(6-tert-butyl-4-methylphenol).…”
Section: Resultsmentioning
confidence: 60%
“…in the material may actually be too low to elicit a positive reaction at ordinary patch testing, even if an extract of the product is made. 2 Producing an extract can in itself be difficult because of the lack of material, especially if extraction solvents with different physico-chemical properties are desired. 1 The culprit contact allergens found have mainly been used in attachment areas, ie, where different materials must adhere to each other, but not necessarily primarily in the adhesive patch in direct contact with the skin.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of IBOA in some medical devices might be underestimated, as recent investigations have shown that some devices, even those once deemed to be free from IBOA, 6 might still contain this sensitizer, depending, among other things, on the specific chemical analytical tools used. 7 The FreeStyle sensor also contains other potential contact allergens but, as recently demonstrated, no PEA. 3 For the observed coreactivity to the PEA-containing patch test preparation and to the other acrylates, possible explanations include: (a) concomitant sensitization from other sources: given that the boy had already been hospitalized several times, he was potentially at increased risk for cutaneous sensitization to (meth)acrylates from various medical devices and adhesives, including the blood pressure cuff that had been repeatedly applied during previous hospitalizations; (b) crossreactivity between IBOA and PEA, and other acrylates, although IBOA has rarely shown any clear cross-reactivity to other acrylates so far; 3,8 and (c) the positive patch test reaction to PEA may actually have been provoked by IBOA, as recent analyses showed that raw materials of PEA obtained from the industry, as in the present case, may contain acrylate contaminants, which include IBOA.…”
Section: Discussionmentioning
confidence: 92%